Wykorzystanie odpadów biodegradowalnych do produkcji biogazu jako alternatywnego źródła energii odnawialnej - Marlena Owczuk; Dorota Wardzińska; Anna Zamojska-Jaroszewicz; Anna Matuszewska (Studia Ecologiae et Bioethicae)
Waste products from the agriculture industry and other sectors are creating a waste problem with a negative environmental impact. Such effects can be minimized by further processing methods. One method, which is gaining increased importance around the world, is anaerobic digestion, for which biodegradable waste is a valuable source of raw material (Ryckebosch et al. 2011; Deublein, Steinhauser 2008). The paper discusses the technological process of biogas production, as well as the most commonly used methods of purification and refining. It also identifies the potential ways of using the resulting product (CHP, biofuels).